The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.14214/sf.1214
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing informal interaction and knowledge co-construction among forest owners

Abstract: • Forest owners' own communities could complement the present expert-driven forestry extension.• Enhancing informal interaction between forest owners calls for sufficiently homogeneous reference groups and also new communication contexts.• New purposes of forest ownership and innovative forest management practices are suggested topics for novel owner communities.• Forest professionals may initiate these communities, but the continuity depends on the owners themselves. AbstractIt is a common concern that non-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
(39 reference statements)
0
11
0
2
Order By: Relevance
“…The masculine culture of emphasising economic forestry may also hinder the realisation of female forest owner's nature-related objectives (Vainio and Paloniemi 2013) or alienate them from forestry if advisory services do not acknowledge them as equal actors in forestry, who nonetheless may have other goals besides timber production. The active participation and agency of women in forestry can be enhanced with gender-specific activities and peer-learning (Hamunen et al 2015), but more important is normalising women's status as forest owners and forest sector actors (Brandth et al 2004). Gender consciousness is important to consider in future research, to ensure the validity of results and comprehensive understanding of forest owner composition.…”
Section: Need For User-oriented Decision Support Services Is Evidentmentioning
confidence: 99%
See 1 more Smart Citation
“…The masculine culture of emphasising economic forestry may also hinder the realisation of female forest owner's nature-related objectives (Vainio and Paloniemi 2013) or alienate them from forestry if advisory services do not acknowledge them as equal actors in forestry, who nonetheless may have other goals besides timber production. The active participation and agency of women in forestry can be enhanced with gender-specific activities and peer-learning (Hamunen et al 2015), but more important is normalising women's status as forest owners and forest sector actors (Brandth et al 2004). Gender consciousness is important to consider in future research, to ensure the validity of results and comprehensive understanding of forest owner composition.…”
Section: Need For User-oriented Decision Support Services Is Evidentmentioning
confidence: 99%
“…However, this discourse has been found to cause stress or pressure to comply with it regardless of whether a forest owner's objectives are non-monetary or a forest is only a minor part of a household's responsibilities (Takala et al 2017b), and hence it risks alienating forest owners from the services and forest management. Because alienated or indifferent forest owners are considered problematic for active forest management and hence meeting policy goals (Follo 2011;Hamunen et al 2015), it is important for forest professionals to recognise different owner motivations and adapt the decision support services accordingly (Takala et al 2017a). Owner-oriented planning and advisory services related to it are guided by forest owner needs, aims and resources (Hujala et al 2007;Hokajärvi et al 2009).…”
Section: Need For User-oriented Decision Support Services Is Evidentmentioning
confidence: 99%
“…As conversações entre membros das comunidades estudadas são oportunizadas de diversas maneiras. Nas comunidades que se valem de encontro face a face, as práticas adotadas são os fóruns, conversas informais, trabalhos conjuntos para a solução de problemas comuns e também trabalhos em times de aprendizagem (Apostolou et al, 2004;Hamunen et al, 2015 impacto limitado, com os membros fazendo contato inicial por meio deles, e continuando por intermédio da troca de mensagens de e-mail (D.E. Topousis et al, 2012).…”
Section: Compartilhamento Mútuounclassified
“…Participants in the FGs also voiced a wish for more opportunities to engage in peer-to-peer 560 discussions concerning the potential of forest use and experiences. Knowledge exchange was 561 studied in a study by Hamunen et al (2015), which concluded that quite a few options for forest 562 owner gatherings already exist, such as basic courses for new forest owners or forest owner 563 clubs. Perhaps there is still a need to more effectively market such events, especially to new 564 forest owners.…”
mentioning
confidence: 99%
“…Perhaps there is still a need to more effectively market such events, especially to new 564 forest owners. Hamunen et al (2015) also suggested more informal communication "circles" 565 between forest owners that could lead to the testing of more innovative forest management 566 practices. As a few participants in the FGs mentioned, previous studies have also shown that forest use, and conservation issues (Vainio and Paloniemi 2013).…”
mentioning
confidence: 99%